Material words: The aesthetic grammar of Toraja textiles, carvings, and ritual language - Donzelli, Aurora (Journal of material culture, 2020)
This article examines the intersections between ritual speech, woodcarving, and painted sacred cloths among the Toraja of upland Sulawesi, Indonesia. The author argues that the longstanding division between studies of speechmaking and material culture has obfuscated significant overlaps between what in fact are related systems of semiotic expressions in Indonesia and beyond. By bringing within a single analytic field the forms of ritual speech, textiles, and woodcarving she documented during long-term intermittent fieldwork in Sulawesi (2002-2018), the author highlights fundamental commonalities in how these different semiotic codes operate and in the local conceptions of authorship and craftsmanship. She shows how key aspects of Toraja vernacular semiotics, aesthetics, and hermeneutics are embedded in a materialist ideology of language and suggests that a joint approach to meaning-making practice across different modalities, channels, and media may further our understanding of Indonesian figurative languages and help delineate the larger cultural poetics underlying Austronesian artistic productions.